PENGARUH DISIPLIN KERJA, MOTIVASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS TENAGA KERJA, TRANSMIGRASI DAN KEPENDUDUKAN PROVINSI JAWA TENGAH - Heronimus Elekstewa, 11.05.51.0091 (Students Journal of Economic and Management, 2015)
This study analyzed the effect of labor discipline, motivation, organizational culture on employee performance. The research object in this paper is the Office of Manpower, Transmigration and Population Central Java. The sampling technique used purposive sampling amounted to 105 respondents in the sample data collection method using a questionnaire by distributing a list of statements to the respondents in order to obtain information. The research objective was formulated to determine the effect of work discipline, motivation, organizational culture on employee performance. File were collected and analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are: (1) Work Discipline, Motivation and Work Environment has a positive and significant impact on employee performance. (2) Cultural Organization has no significant effect on employee performance. Keywords : Work Discipline , Motivation , Organizational Culture , Work Environment, performance